Low temperature internal friction peak in high Tc superconductors - Rodríguez, E.; Luzuriaga, Javier; Núñez Regueíro, M.; Fainstein, Daniel (Comisión Nacional de Energía Atómica; Argentina, 1990)
Fil: Rodríguez, E. Comisión Nacional de Energía Atómica; Argentina